2018
DOI: 10.1186/s11782-018-0025-y
|View full text |Cite
|
Sign up to set email alerts
|

High performance work systems and corporate performance: the influence of entrepreneurial orientation and organizational learning

Abstract: This study investigates the functioning mechanisms of how high performance work systems (HPWS) affect organizational performance. We propose that (HPWS) can positively affect organizational performance through the mediating role of entrepreneurial orientation. An organization with high performance work systems can perform better if it enjoys high level of organizational learning. We design and administer a survey questionnaire to high-level executives or founders of companies from manufacturing and service ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 96 publications
(151 reference statements)
0
47
0
5
Order By: Relevance
“…The work of Zhu et al [20] explained that the relationship between entrepreneurial orientation partially mediates the relationship between high performance work systems and organizational performance, which suggested the significant contribution of the organizational commitment as the element of performance on entrepreneurial orientation. Confirming that, Marshall and Gigliotti in 2020 [19] explained that while entrepreneurial orientation might be started at younger age, it will be more polished within the organization.…”
Section: Discussion and Implicationmentioning
confidence: 99%
See 2 more Smart Citations
“…The work of Zhu et al [20] explained that the relationship between entrepreneurial orientation partially mediates the relationship between high performance work systems and organizational performance, which suggested the significant contribution of the organizational commitment as the element of performance on entrepreneurial orientation. Confirming that, Marshall and Gigliotti in 2020 [19] explained that while entrepreneurial orientation might be started at younger age, it will be more polished within the organization.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…In the recent pre-pandemic era, the main predictors of high turnover intention among millennials were either lower levels of organizational commitment due to mental perceived mental health-related issues [15]- [18] or high levels of entrepreneurial orientation [19], [20]. The two factors were significant because the millennials perceived that they deserve a better work-life balance, and that they have the skills required by the new companies; furthermore, many startup companies developed by millennials would prefer to hire millennial employees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, innumerable researches have been done on HPWS and performance (Úbeda-García, Claver-Cortés, Marco-Lajara, Zaragoza-Sáez, & García-Lillo, 2017;Zhu, Liu, & Chen, 2018) but still there are very limited researches that have been conducted on HPWS and export performance, specifically focusing on dimensions of HPWS. At the same time, there is lack of studies that focused on developing countries, especially in Pakistan's textile sector.…”
Section: Gaps In Literaturementioning
confidence: 99%
“…However, despite these risks, research has shown innovation positively correlates to performance. Zhu, Liu, and Chen (2018) conducted an empirical study indicating the relationship between high-performing work systems and corporate performance and asserted the relationship is more positive when organizational learning is stronger, yielding more significant innovation. Relative to the global staffing industry there are many innovation trends that impact both the industry and its employees alike, which is covered in the next section.…”
Section: The Linkages Between Innovation Organizational Learning Anmentioning
confidence: 99%